Using Google Workspace for Education as a Foundation for Data Governance and Student Services in Higher Education - Sopwandin, Iwan; Junaidi, Akhmad (AL-IDARAH: JURNAL KEPENDIDIKAN ISLAM, 2024)
Student service is one of the indicators to measure the quality of higher education. Its convenience will create comfort for students which will lead to satisfaction; that is one of the assessment aspects in institution accreditation. When the students are satisfied with the service, it will also become a free marketing to the community. This study aims to analyze the use of Google Workspace for Education as a basis for data governance and student services in higher education. The method used in this study was qualitative with a descriptive analysis approach. The data were collected through observation, interviews, and documentation studies. The data analysis techniques were using interactive models of Miles and Huberman that consisted of data condensation, data presentation and conclusions drawing. The validity test of the data was carried out through observation and triangulation. The results of this study indicated that Sekolah Tinggi Ilmu Tarbiyah Az Zahra Tasikmalaya has been using Google Workspace for Education as the basis for data management and student services by utilizing Google Drive, Google Forms, Google Documents, Google Spreadsheets, Google Slides, Google Meet and Google Sites features. These features are used as data storage media, attendance lists, generating certificate, issuing active letter and research permits, webinars, and student admission pages. The impact of using Google Workspace for Education has been greatly perceived by students, as well as by other parties. The use of Google Workspace for Education has given some benefits, namely: 1) Effectiveness, such as a fast service in issuing an active letter for the students that will be sent automatically via email, and non-face-to-face service in administration office unless when there are some problems in its application; 2) Efficiency, for new universities that are still in adjustment, one of which is financial aspect, where Google Workspace for Education can be an alternative that can be used in providing services to students, because the necessary features can be accessed for free.